Characteristics of psychosocial status in women with neuroimaging brain changes due to hiv infection and viral hepatitis C - E. V. Boeva; N. B. Khalezova; V. V. Rassokhin; N. G. Neznanov; E. A. Gromova; A. A. Bogdan; T. N. Trofimova; N. A. Belyakov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The purpose of the study: to give a comprehensive characteristic (clinical-immunological, psychosocial, psychopathological) of women with HIV / viral hepatitis C (HCV) co-infection, to determine the presence of structural and functional changes in the brain using neuroradiological research methods.   Material: The main study group consisted of 200 women with HIV / HCV co-infection and 200 women diagnosed with HIV infection without HCV.   The criteria for inclusion in the study were: age from 18 to 45 years; the presence of a confirmed HIV / HCV co-infection or HCV monoinfection; the absence of the use of psychoactive substances (except alcohol) during 6 months prior to the study; non-pregnant.   Methods: clinical; socio-demographic; laboratory; instrumental. In the future 36 women were selected from the main and comparison groups by the method of paired comparisons, identical to each other in age, at the initial stages of HIV infection, with a CD4 lymphocyte count of over 350 cells/µl; taking antiretroviral therapy for no more than 12 months; not receiving HCV antiviral therapy; without concomitant diseases; not using any substances during 6 months before the study. The studies of the structure and metabolism of the central nervous system were performedthem: magnetic resonance imaging (MRI) and positron emission tomography / computed tomography (PET / CT) with fluorodeoxyglucose (FDG).   Results: Women with HIV / HCV, unlike women with HIV monoinfection, are more predisposed to the development of psychopathological conditions with a significant frequency of asthenic and anxiety disorders against the background of mild and moderate cognitive impairment, which is probably due to both the presence of concomitant HCV and the use of substances in the past. Patients with HIV / HCV revealed neuroradiological features in the form of vascular and HIV-encephalopathic changes, a high incidence of glucose hypometabolism. The relationship between the localization of signs of glucose hypometabolism and the identified anxiety, cognitive and insomniac disorders has been determined. The algorithm of examination and management of patients with HIV infection and HCV is proposed.